Space‐Scale Resolved Surface Fluxes Across a Heterogeneous, Mid‐Latitude Forested Landscape. Issue 23 (1st December 2022) - Paleri, Sreenath; Desai, Ankur R.; Metzger, Stefan; Durden, David; Butterworth, Brian J.; Mauder, Matthias; Kohnert, Katrin; Serafimovich, Andrei
Abstract: The Earth's surface is heterogeneous at multiple scales owing to spatial variability in various properties. The atmospheric responses to these heterogeneities through fluxes of energy, water, carbon, and other scalars are scale‐dependent and nonlinear. Although these exchanges can be measured using the eddy covariance technique, widely used tower‐based measurement approaches suffer from spectral losses in lower frequencies when using typical averaging times. However, spatially resolved measurements such as airborne eddy covariance measurements can detect such larger scale (meso‐ β, meso‐ γ ) transport. To evaluate the prevalence and magnitude of these flux contributions, we applied wavelet analysis to airborne flux measurements over a heterogeneous mid‐latitude forested landscape, interspersed with open water bodies and wetlands. The measurements were made during the Chequamegon Heterogeneous Ecosystem Energy‐balance Study Enabled by a High‐density Extensive Array of Detectors intensive field campaign. We ask, how do spatial scales of surface‐atmosphere fluxes vary over heterogeneous surfaces across the day and across seasons? Measured fluxes were separated into smaller‐scale turbulent and larger‐scale mesoscale contributions. We found significant mesoscale contributions to sensible and latent heat fluxes through summer to autumn which would not be resolved in single‐point tower measurements through traditional time‐domain half‐hourly Reynolds decomposition. We report scale‐resolved flux transitions associated with seasonal and diurnal changes of the heterogeneous study domain. This study adds to our understanding of surface‐atmospheric interactions over unstructured heterogeneities and can help inform multi‐scale model‐data integration of weather and climate models at a sub‐grid scale. Plain Language Summary: Accurate and reliable knowledge of the surface‐atmospheric transport of mass and energy is essential to inform our theories and models of Earth system processes. Conventionally, such transport has been measured by tower‐mounted weather instruments that make high‐frequency measurements. However, experimental and simulation studies over the last couple of decades have shown that there is an imbalance between incoming, available energy and outgoing transport as observed from tower‐mounted setups. A dominant hypothesis addressing this imbalance issue postulates that there exists significant larger landscape scale transport (of the order of 10–100 km) over the course of a day. Single‐point tower measurements would not be able to include such transports in their conventional process flows. We use airborne data collected over a mid‐latitude temperate forest in Northern‐Wisconsin, USA to quantify large‐scale transport over the forested domain. Observations were made over the course of single days in July, August, and September to include seasonal landscape transitions. The measured surface‐atmospheric exchange is resolved into smaller and larger scale contributions using a space‐frequency analysis framework that has been in use for aircraft measured atmospheric data. We report substantial large‐scale contributions with daily, seasonal and spatial characteristics. Key Points: Substantial, persistent mesoscale surface‐atmospheric fluxes were measured across a heterogeneous mid‐latitude forested domain Measured fluxes show distinct seasonal and diurnal variations Measured mesoscale fractions of sensible and latent heat fluxes do not behave similarly